Facile preparation of g-C3N4 modified BiOCl hybrid photocatalyst and vital role of frontier orbital energy levels of model compounds in photoactivity enhancement - Shi, Shan; Gondal, M.A.; Al-Saadi, A.A.; Fajgar, Radek; Kupcik, Jaroslav; Chang, Xiaofeng; Shen, Kai; Xu, Qingyu; Seddigi, Z.S. (Journal of colloid and interface science, 2014)
[Display omitted] •g-C3N4/BiOCl photocatalysts with different molar ratios have been prepared.•The optimal mass ratio in g-C3N4/BiOCl has been confirmed.•The effects of initial concentration and pH of model contaminant have been studied.•The photoactivity enhancement is strongly rely on the LUMO level of dye molecules. A novel hybrid photocatalyst (g-C3N4/BiOCl) using g-C3N4 series modified with BiOCl having controllable mass ratios among the g-C3N4 and BiOCl molecules was prepared through hydrolysis process of Bi3+ onto g-C3N4, using NaBiO3 and g-C3N4 produced from pyrolysis of melamine as the starting materials. The microstructure, morphology and optical properties of the synthesized g-C3N4/BiOCl were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), UV–Vis diffuse reflection spectroscopy (DRS) and photoluminescence (PL) emission spectroscopy. The photoactivity of the g-C3N4/BiOCl was evaluated by photodegradation of Rhodamine B(RhB) from water as a model toxic contaminant. The RhB photodegradation results revealed that the photocatalytic activity of g-C3N4/BiOCl hybrid photocatalyst (mass ratio of g-C3N4/BiOCl equals to 2:8) exhibits superior activity as compared with pure BiOCl under visible light irradiation. The effects of pH, initial concentration of the model contaminant as well as the catalyst recycling on the photoactivity (or photostability) of g-C3N4/BiOCl were investigated in depth as well. Quantum chemical calculations revealed that the photoactivity enhancement is strongly dependent on the active role played by the frontier orbital energy levels of dye molecules and a probable correlation of “structure–activity” relationship was established.